Kant's dynamic metaphysics: kant's theory of judgment and the nature of the theoretical knowledge of consistency in empirical reasoning - Lucas Vollet (Griot: Revista de Filosofia, 2023)
Kant's theory of judgment involves his answer to the question "How is knowledge of the pattern underlying intentional strategies of objective - true and justified - representation of empirical events possible?" When we problematize this question, the problem of the scope of our notion of consistency in empirical reasoning emerges. We will argue in this article that Kant's theory includes a thesis about the circular nature of our patterns of consistency, based on the ability to protect the conceptual presuppositions that harmonize knowledge of truth as opposed to falsity in any paradigm of theoretical reflection. This thesis allows Kant to develop a foundationalism about the knowledge of the content of judgments (the ability to recognize conceptual correctness or rule consistency) without committing to a static and transcendent view of the ideal object of our assertion strategies. In our view, this view is still one of the most competitive in describing the necessary - though not static - status of the propositions of empirical science.